Nurturing Habits of Mind (HOM) Through Thinking Based Learning (TBL) in Doing Science Technology, Engineering and Mathematics (STEM) Project - Hashim, Hartini; Ali, Mohd Norawi; Samsudin, Mohd Ali (EDUCATUM Journal of Science, Mathematics and Technology, 2018)
Habits of mind (HOM) is one of the kind response to those questions and problems whereby the answers to which are not immediately known which can attribute to effective problem solvers and critical thinking development. However, the emphasis on this aspect is still low especially among science educators as well as secondary science students which in the long run will retard the production of knowledge worker who are able to behave when confronted with life’s problems. The study addressed the integration of Thinking Based Learning (TBL) and the 6E Instructional Model as a teaching approach in nurturing habits of mind among secondary students while doing their Science, Technology, Engineering and Mathematics (STEM) project. The study involved 30 students from a Lower Secondary School in a sub urban school in Kota Bharu, Kelantan. Students were given a STEM Raft Module integrating TBL and 6E Instructional Model for five weeks to come out with a model of a raft based on science concepts using material available in their community. Data of the study were captured from students’ documentation analysis, classroom observation using camera and video cam recording, and interview. The findings showed that TBL and 6E Instructional Model can nurture habits of mind among secondary students while doing their STEM project. Seven characteristics of habits of mind have been identified; (1) questioning and problem solving, (2) listening with understanding and empathy, (3) thinking about your thinking, (4) thinking flexibility, (5) applying past knowledge to novel situations, (6) creating, imagining and innovating and (7) thinking independently. Keywords: Habits of mind, Thinking Based Learning, the 6E Instructional Model, STEM project